A STUDY OF KNOWLEDGE AND PERCEPTION ON BIODIVERSITY AMONG THE UNDERGRADUATE STUDENTS OF ALLIED HEALTHCARE SCIENCES, MRU, HYDERABAD - Meera Indracanti, Muni Kumar Dokka, Pavan Chand Akkiraju, (Chelonian Research Foundation, 2023)
The present study was carried out to assess the knowledge and perception of biodiversity and its protection and conservation amongst first-year undergraduate students at the School of Allied Healthcare Sciences, Malla Reddy University, Hyderabad, India. An institutional-based cross-sectional study was conducted from July 3 to 25, 2023. A self-administered questionnaire was used to collect data on socio-demographics, knowledge, and perception of biodiversity. Data were consolidated, coded, transferred, and analyzed with SPSS version 25. Three hundred forty-one students have participated, with a 100% response rate. More than 50% (N=179) of students had low knowledge scores on biodiversity, and 11.1% (N=38) showed negativity. Most students (86.2%) were aware that biodiversity loss leads to floods and global warming, and 89.7% of students believed they could do something to protect the world's biodiversity. Chi2 test of the independent analysis showed that the Branch of study (BOS) and Family Income (FI) have a relationship with knowledge score, and the girls had a better perception (7.4; p=0.05) over boys. Pearson's correlation analysis between knowledge and perception scores showed a weak correlation (r=0.154 at p=0.01). The present study revealed that the respondents had a moderate level of knowledge about biodiversity, and most of the students have a moderately positive attitude towards biodiversity and find themselves engaging in topics related to environmental behavior. Keywords: Attitude, Biodiversity, Correlation, Ecosystem, Socio-demographic.